Phylogenetic Clades 6 and 8 of Enterohemorrhagic Escherichia coli O157:H7 With Particular stx Subtypes are More Frequently Found in Isolates From Hemolytic Uremic Syndrome Patients Than From Asymptomatic Carriers. (12th August 2014) - Iyoda, Sunao; Manning, Shannon D.; Seto, Kazuko; Kimata, Keiko; Isobe, Junko; Etoh, Yoshiki; Ichihara, Sachiko; Migita, Yuji; Ogata, Kikuyo; Honda, Mikiko; Kubota, Tsutomu; Kawano, Kimiko; et al.
Abstract : EHEC O157:H7 clade 6 strains harboring stx2a and/or stx2c and clade 8 strains harboring stx2a or stx2a / stx2c were frequently associated with childhood HUS cases in Japan. Rapid and specific detection of such lineages are required for infection control measures. Abstract: Background.  Enterohemorrhagic Escherichia coli (EHEC) O157:H7 infection causes severe diseases such as bloody diarrhea and hemolytic uremic syndrome (HUS). Although EHEC O157:H7 strains have exhibited high genetic variability, their abilities to cause human diseases have not been fully examined. Methods.  Clade typing and stx subtyping of EHEC O157:H7 strains, which were isolated in Japan during 1999–2011 from 269 HUS patients and 387 asymptomatic carriers (ACs) and showed distinct pulsed-field gel electrophoresis patterns, were performed to determine relationships between specific lineages and clinical presentation. Results.  Clades 6 and 8 strains were more frequently found among the isolates from HUS cases than those from ACs ( P = .00062 for clade 6, P < .0001 for clade 8). All clade 6 strains isolated from HUS patients harbored stx2a and/or stx2c, whereas all clade 8 strains harbored either stx2a or stx2a / stx2c . However, clade 7 strains were predominantly found among the AC isolates but less frequently found among the HUS isolates, suggesting a significant association between clade 7 and AC ( P < .0001). Logistic regression analysis revealed that 0–9 year old age is a significant predictor of the association between clade 8 and HUS. We also found an intact norV gene, which encodes for a nitric oxide reductase that inhibits Shiga toxin activity under anaerobic condition, in all clades 1–3 isolates but not in clades 4–8 isolates. Conclusions.  Early detection of EHEC O157:H7 strains that belonged to clades 6/8 and harbored specific stx subtypes may be important for defining the risk of disease progression in EHEC-infected 0- to 9-year-old children.